Activity enhancement of carbon nanofiber-based catalysts for CO2 methanation by mechanochemical synthesis - Christian Di Stasi; Jaime López-de los Ríos; Alejandro Ayala-Cortés; Daniel Torres; José Luis Pinilla; Isabel Suelves (Journal of CO2 Utilization)
Carbon nanofibers (CNFs) modified with CeO2 were employed as support for the synthesis of Ni catalysts for the CO2 methanation reaction. Two different preparation methods were investigated: incipient wetness impregnation and mechanochemical synthesis. The catalysts were tested at atmospheric pressure under a wide range of temperatures (200 – 600 °C) using a stoichiometric ratio of undiluted H2/CO2 and a flow to weight ratio of 600 NL h−1 gNi−1. The results showed that the Ni-CeO2/CNF catalyst prepared by mechanochemical synthesis showed higher CO2 conversion and CH4 selectivity at low temperatures than the one prepared via traditional method. This was attributed to smaller Ni crystallites and to the higher quantity of Ce3+ sites exposed by the milling process. Stress test carried out at 450 °C showed that the activity and the reaction mechanism remained stable for at least 50 h.